2006
DOI: 10.1186/1471-2458-6-109
|View full text |Cite
|
Sign up to set email alerts
|

The silent HIV epidemic among pregnant women within rural Northern Tanzania

Abstract: Background: Many national antenatal clinics (ANC) based HIV surveillance systems in subSaharan Africa have limited coverage of remote rural sites, a weakness that compromises adequate estimation, monitoring and development of effective preventive and care programmes. To address this void in rural Manyara and Singida within Northern Tanzania, we conducted antenatal clinicbased sentinel surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
23
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
(26 reference statements)
7
23
0
Order By: Relevance
“…Figures from 2009 estimate a prevalence of 5.6% among adults (aged 15-49) at a national level (UNAIDS, 2010) in Tanzania, compared to a prevalence of 8.8% in 2003(UNAIDS et al, 2004. In the study area the HIV prevalence is lower and has been estimated to be 2% among women and men aged 15-49 (TACAIDS, 2005), confirmed by the study of Yahya-Malima et al (2006) among antenatal clinic attendees.…”
Section: Study Contextmentioning
confidence: 68%
“…Figures from 2009 estimate a prevalence of 5.6% among adults (aged 15-49) at a national level (UNAIDS, 2010) in Tanzania, compared to a prevalence of 8.8% in 2003(UNAIDS et al, 2004. In the study area the HIV prevalence is lower and has been estimated to be 2% among women and men aged 15-49 (TACAIDS, 2005), confirmed by the study of Yahya-Malima et al (2006) among antenatal clinic attendees.…”
Section: Study Contextmentioning
confidence: 68%
“…A population of replacement blood donors was studied in order to avoid the numerous biases inherent in studies of voluntary blood donors [Sedyaningsih-Mamahit et al, 2004]. As previously reported [Yahya-Malima et al, 2006], high educational status was over-represented among voluntary donors.…”
Section: Discussionmentioning
confidence: 98%
“…However, several studies [Chilundo and Sahay, 2005;Goncalez et al, 2006] have shown that the voluntary donor population provides a biased view of the epidemiological situation, owing to explicit or implicit selection criteria that tend to eliminate those who are ill or at risk; indeed, low-risk groups are selected in order to improve transfusion safety. Among volunteer donors, individuals with high sociocultural status and urban dwellers both tend to be over-represented, while rural populations are under-represented [Yahya-Malima et al, 2006]. ''Replacement donors'' contribute largely to the transfusion system in Mozambique, and are used to palliate the lack of blood products.…”
Section: Human Immunodeficiency Virus (Hiv) Hepatitis B Virus (Hbv)mentioning
confidence: 99%
“…In India, HIV prevalence found in a populationbased study was much lower than that obtained through a sentinel study of prenatal clinics [11]. On the other hand, incomplete coverage of the sentinel network in African countries, which fail to reach rural and remote areas, can underestimate HIV prevalence in these countries [12].…”
mentioning
confidence: 79%